2021
DOI: 10.4274/tjod.galenos.2020.21703
|View full text |Cite
|
Sign up to set email alerts
|

Blake’s pouch cyst: Prenatal diagnosis and management

Abstract: Objective: This study aimed to present the characteristic features of 19 patients who were diagnosed as having Blake’s pouch cyst (BPC) at our center. Materials and Methods: Nineteen patients diagnosed as BPC between 2015 and 2019 were included in this retrospective study. Follow-up examinations were performed using ultrasonography (US) every three weeks up to 35 weeks of gestation. Prenatal magnetic resonance imaging (MRI) was performed at the time of diagnosis or duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the prenatal ultrasound community, the 4V-CP entered the diagnostic arena only after the description, by Tortori-Donati et al in 1996 16 , of Blake's pouch cyst (BPC) as a pathological entity distinct from mega cisterna magna in neonates. Subsequently, BPC was also demonstrated in the fetus [17][18][19] and it was established that one of the fundamental distinctive diagnostic criteria of BPC is a normal size of the vermis, unlike that which is observed in vermian hypoplasia (VH) and Dandy-Walker malformation (DWM) 17 . However, in a small number of cases, sonographic assessment of vermian biometry is not able to differentiate between BPC and VH.…”
Section: Sonographic Position Of the 4v-cp In Relation To Cystic Abnormalities Of The Posterior Fossamentioning
confidence: 99%
“…In the prenatal ultrasound community, the 4V-CP entered the diagnostic arena only after the description, by Tortori-Donati et al in 1996 16 , of Blake's pouch cyst (BPC) as a pathological entity distinct from mega cisterna magna in neonates. Subsequently, BPC was also demonstrated in the fetus [17][18][19] and it was established that one of the fundamental distinctive diagnostic criteria of BPC is a normal size of the vermis, unlike that which is observed in vermian hypoplasia (VH) and Dandy-Walker malformation (DWM) 17 . However, in a small number of cases, sonographic assessment of vermian biometry is not able to differentiate between BPC and VH.…”
Section: Sonographic Position Of the 4v-cp In Relation To Cystic Abnormalities Of The Posterior Fossamentioning
confidence: 99%
“…After diagnosing FCMs, amniocentesis and/or karyotype analysis are performed to detect congenital cardiac anomalies, other multiple anomalies and genetic etiology (9). Bahram et al (10) reported that all of these fetuses had multiple anomalies, although the termination rate was reported as 26.0% in which pregnant women with fetal cerebellar anomaly (Blake's pouch cyst).…”
Section: Introductionmentioning
confidence: 99%